(3eSDhdjI GdefJL aj GdbhGfjf GdeOfjI h GdGJaGbjGJ GdOhdjIs - (3SGde eMeO QOjYGf(B, (3GdYRGhjs ((3YeGf(B:s (3OGQ GdKbGaI ddfTQ h GdJhRjY(B,s, 2008)
(3jfMUQ ehVhY gPg GdOQGSI deSDhdjI GdefJL aj GdeSDhdjI GdeOfjI Yf GdCVQGQ GdJj JUjH GdeTJQj Ch GdMGFR ddefJhL aj TNUg Ch CehGdg (B"(3GdCVQGQ GdLSeGfjI hGdeGdjI(B" (3hJQcR Ydi GdVQQ GdLSeGfj dchfg GdCcKQ TjhYkG aj ejOGf GdeSDhdjI Yf GdefJLGJ EVGaI Edi Cfg GdVQQ GdPj hdOJ gPg GdeSDhdjI CUdkG ef CLd JZWjJg, HjfeG GdVQQ GdPj jUjH GdCehGd Ch GdeeJdcGJ de jONd aj fWGb gPg GdeSDhdjI EdG aj GdSfhGJ GdCMjQI bjGSkG Ydi GdVQQ GdLSeGfj ef LQGA faS GdMGOK hdPdc EPG eG CQOfG JhNj GdObI dJMOjO ehVhY gPg GdOQGSI HTcd COb fbhd, HCfgG JOQS ehVhY (B((3GdeSDhdjI GdeOfjI ddefJL GdHGFY Yf GdVQQ GdLSeGfj GdfGTF Yf GdefJLGJ GdVGQI HSHH YjhHgG Ch WHjYJgG GdNWQI(B). (3JCSjSkG Ydi eG JbOe LGAJ NWI GdQSGdI PGJ JbSje KfGFj JJhRY aUhdgG Ydi HGHjf bOe dgeG HaUd JegjOj JfGhd eSDhdjI GdefJL HhLg YGe, hNUU GdHGH GdChd ddcdGe Ydi GdJMOjO GdbGfhfj dHYV GdeaGgje GdbGfhfjI GdCSGSjI aj gPg GdeSDhdjI GdLOjO cGdefJL hGdefJhL hGdYjH aj GdefJLGJ, HjfeG JfGhd GdHGH GdKGfj GdCSGS GdbGfhfj deSDhdjI GdefJL(B.s
(3HjdjhZQGajG U(B.393s
Keywords: (3GdGJaGbjGJ GdOhdjIs; (3GdbGfhf GdeOfjs